2018
DOI: 10.1007/s00590-018-2189-8
|View full text |Cite
|
Sign up to set email alerts
|

Second-site prosthetic joint infection in patients with multiple prosthetic joints

Abstract: Higher morbidity and use of hospital resources are associated with this cohort of patients. PJIs in total knee replacements and positive MRSA status are associated with higher rates of second infection. Identifying this vulnerable cohort of patients at an early stage is critical to ensure measures are taken to reduce the risks of further infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Interestingly, we observed just two cases of re-infection at the same site by a different pathogen [ 3 , 26 ] since it is usually reported that high virulence microorganisms can promote reinfection with the same pathogen [ 27 ]. Here, we reported a re-infection at the same site by Abiotrophia defectiva and Finegoldia magna after successfully treating Staphylococcus warneri and Staphylococcus aureus infections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed just two cases of re-infection at the same site by a different pathogen [ 3 , 26 ] since it is usually reported that high virulence microorganisms can promote reinfection with the same pathogen [ 27 ]. Here, we reported a re-infection at the same site by Abiotrophia defectiva and Finegoldia magna after successfully treating Staphylococcus warneri and Staphylococcus aureus infections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PJI, as defined by MSIS criteria in this report, are a potentially devastating complication of TJA78). Although there is abundant literature available on primary PJI, the risk factors and clinical outcomes for multiple PJI are less well understood91011). A limited set of case series have estimated the risk of multiple PJI to be between 6.3% to 20% after the development of an index infection in patients with multiple TJA611121314).…”
Section: Discussionmentioning
confidence: 90%
“…In patients with multiple PJI, the large majority of observed infections are likely to be metachronic rather than synchronic1112131415). For example, Jafari et al13) retrospectively observed a population with multiple PJI and found a mean time to second infection of 2.0 years (range, 0–6.88 years) with only 3% of patients in the study suffering from synchronic PJI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attributed the lower rate of eradication of MRSA estimated at 40 to 80%, 21 even in a two-stage resection arthroplasty, to the increased risk of developing a second PJI. Clesham et al 22 identified MRSA and longer hospital length of stay as risk factors for MPJI; the authors also noted that an index infection of a knee prosthesis was associated with a higher risk of developing a second site infection compared with an index hip prosthesis infection. The authors found no correlation between diabetes, chronic obstructive pulmonary disease, hypertension, atrial fibrillation, RA or ischemic heart disease, and the risk of a second MPJI.…”
Section: Risk Factors For Metachronous Periprosthetic Joint Infectionmentioning
confidence: 99%